2018
DOI: 10.1111/nph.15366
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of invasion for pollen transfer and pollination revealed in a tropical island ecosystem

Abstract: Pollination is known to be sensitive to environmental change but we lack direct estimates of how quantity and quality of pollen transferred between plant species shifts along disturbance gradients. This limits our understanding of how species compositional change impacts pollen receipt per species and structure of pollen transfer networks. We constructed pollen transfer networks along a plant invasion gradient in the Hawaiian dry tropical forest ecosystem. Flowers and stigmas were collected from both native an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 66 publications
(94 reference statements)
2
58
1
Order By: Relevance
“…In a recently published meta‐analysis, Arceo‐Gómez and Ashman () found that invasive HP donors reduced fruit and seed production of recipients to a greater degree than native HP donors did, but to our knowledge, the effect of native HP donors on the pollination success of invasive species has not been evaluated. Knowledge on the differential responses to HP between native and invasive plants could help us understand the mechanisms that facilitate plant invasion in natural communities (Arceo‐Gómez and Ashman, ; Johnson and Ashman, ; Takemori et al., ). For instance, invasive species are able to fully integrate into native plant–pollinator networks (e.g., Lopezaraiza‐Mikel et al., ; Vilà et al., ; Maruyama et al., ; Tylianakis and Morris, ) which can be aided, at least partially, by a high level of tolerance to HP from native species, thus enhancing their success in invading new communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published meta‐analysis, Arceo‐Gómez and Ashman () found that invasive HP donors reduced fruit and seed production of recipients to a greater degree than native HP donors did, but to our knowledge, the effect of native HP donors on the pollination success of invasive species has not been evaluated. Knowledge on the differential responses to HP between native and invasive plants could help us understand the mechanisms that facilitate plant invasion in natural communities (Arceo‐Gómez and Ashman, ; Johnson and Ashman, ; Takemori et al., ). For instance, invasive species are able to fully integrate into native plant–pollinator networks (e.g., Lopezaraiza‐Mikel et al., ; Vilà et al., ; Maruyama et al., ; Tylianakis and Morris, ) which can be aided, at least partially, by a high level of tolerance to HP from native species, thus enhancing their success in invading new communities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, invasive plants can alter pollinator visitation quality by increasing heterospecific pollen (hereafter, HP) deposition from IS onto the stigmas of native species (e.g., Lopezaraiza‐Mikel et al., ). This latter mechanism has been increasingly studied (see Bartomeus et al., ; Morales and Traveset, ; Arceo‐Gómez and Ashman, ; Bruckman and Campbell, ), and evidence has accumulated indicating that HP transfer within co‐flowering communities is common (e.g., Ashman and Arceo‐Gómez, ; Fang and Huang, ; Johnson and Ashman, ). Less studied, however, are the potential effects of HP transfer from natives to stigmas of IS (Arceo‐Gómez and Ashman, ), even though it is likely that HP transfer between invasive and native plants is not unidirectional (from invasive to native only).…”
mentioning
confidence: 99%
“…However, patterns for the intensity or quantity of pollen transfer, i.e. the amount of CP / HP pollen received or donated, are not well explained by floral traits [7,26].…”
Section: Introductionmentioning
confidence: 97%
“…Associations between floral traits, HP reception or donation and network properties are variable and even contradictory [3,26,27]. In general, stigma size, flower symmetry and floral size increase the likelihood and intensity of HP reception [3,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation